The Future of the Law of the Sea 2017
DOI: 10.1007/978-3-319-51274-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Private Maritime Security Contractors and Use of Lethal Force in Maritime Domain

Abstract: 2 For more information, especially with regard to the soft-law bottom-up approach to the regulation of private maritime security companies, see: Mudrić (2015a), pp. 53-55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Apart from being expensive and difficult to maintain, naval forces are politically complicated -the minority of countries enjoys the presence of foreign warships in their territorial waters. Marin et al (2017) highlight, that "following the plight of individual coastal states (most notably, the United States) and certain parts of the shipping industry, more and more nongovernmental actors became reliant on the private maritime security services within a short period of time. .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from being expensive and difficult to maintain, naval forces are politically complicated -the minority of countries enjoys the presence of foreign warships in their territorial waters. Marin et al (2017) highlight, that "following the plight of individual coastal states (most notably, the United States) and certain parts of the shipping industry, more and more nongovernmental actors became reliant on the private maritime security services within a short period of time. .…”
Section: Resultsmentioning
confidence: 99%
“…Violent incidents with murder at sea have been reported to be on an increasing rate. Marin et al (2017) concluded that "growing number of reports indicate possible excessive behaviour of individually armed security guards" (p. 195). This tendency throws a shadow on the general credibility of private maritime security contractors.…”
Section: Private Maritime Security Companies At Combatting Piracymentioning
confidence: 99%
See 1 more Smart Citation
“…116 Nonetheless, the issue of human rights at sea also views the phenomenon of private maritime security contractors as a "possible insecurity factor, leading to an increased level of violence and increased insecurity of people and goods at sea." 117 The 2007 Nisour Square massacre incident provides a perspective for consideration. In this incident, a private military company (then known as Blackwater Security Consulting) contracted by the US government to protect US diplomats in Iraq was escorting a US embassy convoy, which led to the shooting of Iraqi civilians: killing 17 and injuring 20 in Nisour Square, Baghdad.…”
Section: Seafarers Crew Members and Master Of A Ship -The Right To Lifementioning
confidence: 99%